Pendampingan Re-Akreditasi SMP Takhassus Al-Qur’an Melalui Penilaian Kinerja Kepala Sekolah - Masrokhan Iskhaq; Hafid Aminudin; Robingun Suyud El Syam; Machfudz Machfudz (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2022)
The school principal's performance assessment is a form of evaluating the quality of the implementation of the main tasks and functions of the school principal in carrying out managerial and supervisory functions in the institution he leads. This activity is important to do in order to know the quality of the school principal's performance. The stages passed: forming the Foundation PKKS team, formulating the PKKS format, socializing the PKKS agenda, coaching from supervisors, PKKS visits, and submitting findings. The results showed that the school principal's performance assessment found incomplete documents so that it was recommended that the school make improvements that could help prepare the school for re-accreditation.